2005
DOI: 10.1523/jneurosci.2431-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ventral Frontostriatal Circuitry in Reward-Based Learning in Humans

Abstract: This study examined changes in behavior and neural activity with reward learning. Using an event-related functional magnetic resonance imaging paradigm, we show that the nucleus accumbens, thalamus, and orbital frontal cortex are each sensitive to reward magnitude, with the accumbens showing the greatest discrimination between reward values. Mean reaction times were significantly faster to cues predicting the greatest reward and slower to cues predicting the smallest reward. This behavioral change over the cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
159
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(175 citation statements)
references
References 53 publications
15
159
1
Order By: Relevance
“…Importantly, among adolescents the regions that are activated during exposure to social stimuli overlap considerably with regions also shown to be sensitive to variations in reward magnitude, such as the ventral striatum and medial prefrontal areas (cf. Galvan et al, 2005;Knutson et al, 2000;May et al, 2004). Indeed, a recent study of adolescents engaged in a task in which peer acceptance and rejection were experimentally manipulated (Nelson et al, 2007) revealed greater activation when subjects were exposed to peer acceptance, relative to rejection, within brain regions implicated in reward salience (i.e., the ventral tegmental area, extended amygdala, and ventral pallidum).…”
Section: Remodeling Of the Dopaminergic System At Pubertymentioning
confidence: 99%
“…Importantly, among adolescents the regions that are activated during exposure to social stimuli overlap considerably with regions also shown to be sensitive to variations in reward magnitude, such as the ventral striatum and medial prefrontal areas (cf. Galvan et al, 2005;Knutson et al, 2000;May et al, 2004). Indeed, a recent study of adolescents engaged in a task in which peer acceptance and rejection were experimentally manipulated (Nelson et al, 2007) revealed greater activation when subjects were exposed to peer acceptance, relative to rejection, within brain regions implicated in reward salience (i.e., the ventral tegmental area, extended amygdala, and ventral pallidum).…”
Section: Remodeling Of the Dopaminergic System At Pubertymentioning
confidence: 99%
“…The vSTR, which includes the nucleus accumbens, is sensitive to both reward magnitude (Galvan et al, 2005) and probability (Pagnoni et al, 2002) and has been shown to be active in response to drug cues (David et al, 2005;Kilts et al, 2001). At the same time, another event-related study observed decreased cue reactivity in the nucleus accumbens of smokers (Due et al, 2002).…”
Section: Cravingmentioning
confidence: 99%
“…Again, the daMCC is but one component of reward circuits that include the striatum, nucleus accumbens, and OFC (Galvan et al, 2005;Haber and Brucker, 2009;Schultz et al, 2000;Ullsperger and von Cramon, 2003); just as it is a component of CFP cognitive-attention networks. Given this, daMCC dysfunction could directly and/or indirectly lead to all of the cardinal signs of ADHD (inattention, impulsivity, and hyperactivity), and could explain the observation that ADHD subjects can perform well when motivated on some tasks, but may perform poorly when the task is not interesting.…”
Section: Cfp Attention Networkmentioning
confidence: 99%